Factors affecting the independence and reliability of Science and how these are perceived - Florides, Georgios A.; Christodoulides, Paul (My University, 2023)
Science studies natural phenomena or uses laws, theories, models and mechanisms to explain them, which are revised when new evidence emerges. However, Science cannot give answer to all questions that may arise. The benefits of science are well known and there is no reason to expand on them. It is of interest though to examine the structure and factors that influence the scientific world and may hold it back from offering greater benefits to mankind. The current study is concerned with the question whether or not Science is independent and reliable. Social and political reasons can direct substantive research in specific areas, but they can also encourage the promotion of unfounded theories. External factors such as prejudice against new ideas and understanding of natural happenings can negatively affect the objectivity of Science. Such factors examined in this paper and influence Science are: Research funding, policy makers and industry; Journal editors; Dogma; Theories declared as Conspiracies; Mutual interests in Academia; Knowledge control, cover ups and war superiority. The above factors can be used negatively to restrain serious scientists from expressing educated opinions and publishing them in scientific journals. In this way healthy discussions between 'opposing parties' are restricted, with Science being the victim as no sound conclusions and consensus on important subjects are reached. To check how the above positions are perceived by the scientific community, a questionnaire was circulated among scientists in 11 countries. Analyzing the 106 responds that were anonymously received, indicated that the respondents were largely in line with the expressed positions of the present paper. It is proposed that the real answer to minimize the effect of the factors that influence Science negatively, is educating people's critical abilities and considering nothing for granted-especially under the influence of powerful Media-unless its validity is independently checked and verified.
Keywords: Academia; Conspiracy; Dogma; Journal editors; Knowledge control; Research funding; War superiority